Обзор работ по флоре и растительности городов (Географический вестник=Geographical bulletin, 2017)
Дается тематико-хронологический анализ всей отечественной и зарубежнойбиблиографии по флоре и растительности городов, что позволяет развенчатьукоренившееся представление о полном или почти полном отсутствии подобныхисследований в нашей науке в прошлом.REVIEW OF PUBLISHED WORKS IN FLORA AND VEGETATION OF TOWNS AND CITIESSubject-chronological analysis of the entire national and foreign bibliography in flora and vegetation of cities is given in order to debunk the entrenched idea of the complete or nearly complete absence of similar studies in our science in the past.